Complete mitochondrial genome of Promethis valgipes valgipes (Marseul) (Insecta: Coleoptera: Tenebrionidae). Issue 2 (1st February 2021) - Bai, Yu; Chen, Jun; Li, Guoyong; Luo, Jianlin; Wang, Hui; Yang, Yang; Liang, Sheng; Ouyang, Bocheng
Abstract: Promethis valgipes valgipes (Marseul) is one of the important fungus-eating beetle distributed in central China, Korea, and Japan. Beetles were obtained from Pizhou City and the species' mitochondrial genome was characterized (GenBank accession number MW201671). The mitogenome consists of a circular DNA molecule of 15, 801 bp, with 68.51% AT content. It comprises 13 protein-coding genes (PCGs), 22 tRNA genes, and two rRNA genes. The PCGs have typical ATN (Met) start codons, except nad1 (TTG as start codon), and are terminated by typical TAN stop codons.